Choice criteria for mobile telecom operator: empirical investigation among Malaysian customers - Rahman, Sabbir; Haque, A. K. M. Ahasanul; Ahmad, Mohd Ismail Sayyed (American Scholars Press, Inc., 2011)
The purpose of this paper is to investigate the choice criteria for a mobile phone operator in the Malaysian Mobile Telecom market by the customers. Structural equation models were applied to test the propositions by means of a survey of a random sample of 400 mobile telecom customers from major cities in Malaysia. It was found that the price and service quality hypothesis are more important than the brand image hypothesis. From this research, mobile telecom managers can learn and plan to offer attractive offer in the market that meet Malaysian customers’ needs.